Pemahaman Siswa pada Materi Bentuk Aljabar melalui Model Discovery Learning dengan Mind Mapping - Muliana Muliana; M Ikhsan; Mukhlis Hidayat (Universitas Syiah Kuala, 2020)
The learning model is a fundamental model used for designing the learning. The learning model to encourage students' engagement recommended by the 2013 Curriculum is the discovery learning model. At the end of this model, students are guided to make conclusions from the materials studied by making a summary in the form of mind mapping. This study aimed to investigate the level of student understanding and student responses to the topic of algebraic form through discovery learning models with mind mapping. This study used a quantitative approach with the type of Pre-Experimental Design research through the One-Shot Case Study design. To test the hypothesis in this study, the t-test was used. The samples were Year 27 Year 7 students in one of the junior high schools in Banda Aceh, Indonesia. This research showed that: 1) students' understanding using the discovery learning model with mind mapping could reach a high or moderate level for the topic of algebraic form; 2) most students' understanding was at the moderate level (59.26%), and 3) the results of student responses of algebraic form using discovery learning model with mind mapping showed good understanding.